Estrutura informacional e clivagem: análise da veiculação de informação em construções clivadas do português brasileiro contemporâneo escrito - Aleixo, Felipe [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this functionalist study, we described and analysed the cleft constructions in the written contemporary Brazilian Portuguese language with the central aim of analysing how information is conveyed by the focal constituents of such sentences. Additionally, we aimed at perceiving whether information is capable of motivating the use of a given kind of cleft structure instead of other. For this purpose, we selected five kinds os cleft constructions: Per Se Clefts (CLIV), É Que Constructions (É QUE), Que Constructions (QUE), Wh-clefts Constructions (PC) and Ser Focus Constructions (SER) (PRINCE, 1979; BRAGA, 1989; LONGHIN, 1999), which composed our research corpus, with a total of 127 occurrences, taken from 1208 written enunciation mode texts in the Portuguese language. These texts are in the main sections of Folha de S. Paulo newspaper and were written during january, 2014. Methodologically, we adopted a qualiquantitative perspective, in which data were analysed in accordance with six factor groups: informational status, denotata activation level, grammatical category, syntactic function, dimension and contrast - all these factors are analysed in relation to the focal constituents of the cleft sentences. The data codification was held by means of GoldVarb X software, aiming at obtaining the frequency statistical results and aiming at carrying out the crossed tabulation between the cleft sentences informational status frequency and the frequency of each syntactic-discoursive parameter. With the obtained results, we perceived that the informational status keeps strong relation with the production of grammatical categories (like noun phrases), of syntactic functions (like subjects and circumstantials) and, especially, with the dimension of the focal constituents (short = given information; medium and long = new information). The factor groups activation level and contrast of the focal constituents did...

Neste estudo funcionalista, descrevemos e analisamos as construções clivadas do português brasileiro contemporâneo escrito com o objetivo central de analisar como a informação é veiculada pelos constituintes focais dessas sentenças. Além disso, buscamos perceber se a informação pode motivar o uso de um determinado tipo de estrutura clivada em detrimento de outro. Para isso, elegemos cinco tipos de construções clivadas, a saber, Clivadas Propriamente Ditas (CLIV), Construções É Que (É QUE), Construções Que (QUE), Construções Pseudoclivadas (PC) e Construções Foco Ser (SER) (PRINCE, 1979; BRAGA, 1989; LONGHIN, 1999), que compõem o nosso córpus de pesquisa, com um total de 127 ocorrências, extraídas de 1208 textos da modalidade de enunciação escrita do português. Esses textos fazem parte dos principais cadernos do jornal Folha de S. Paulo e foram produzidos durante o mês de janeiro de 2014. Metodologicamente, adotamos uma perspectiva quali-quantitativa, em que os dados foram analisados de acordo com seis grupos de fatores, a saber: estatuto informacional, grau de ativação dos referentes, categoria gramatical, função sintática, dimensão e contraste - todos esses fatores são analisados diante dos constituintes focais das sentenças clivadas. A codificação dos dados foi operacionalizada por meio do software GoldVarb X, a fim de obter os resultados estatísticos de frequência e a fim de realizar a tabulação cruzada entre a frequência do estatuto informacional das sentenças clivadas e a frequência de cada parâmetro sintático-discursivo. Por meio dos resultados obtidos, vimos que o estatuto informacional mantém forte relação com a produção de categorias gramaticais (como sintagmas nominais), de funções sintáticas (como sujeitos e circunstanciais) e, sobretudo, com a dimensão dos constituintes focais (curtos = informação dada; médios e longos = informação nova). Os grupos de fatores...
Keywords: Linguística; Língua portuguesa; Gramatica comparada e geral - Sintaxe; Linguistics